2022
DOI: 10.1002/cac2.12382
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal TMEM9‐LAMTOR4‐controlled mTOR signaling integrity is required for mammary tumorigenesis

Abstract: Lysosomes play vital roles in the degradation and recycling of various macromolecules, protein secretion, energy metabolism, and cell signaling. Increasing evidence suggests that deregulated lysosomes contribute to tumorigenesis. However, the underlying mechanisms of lysosomal deregulation in cancer remain elusive. We herein identified transmembrane protein 9 (TMEM9) as a crucial protein that modulates lysosomal metabolism and lysosome-associated signaling.The TMEM9 gene is markedly amplified in breast cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…It has been reported that TMEM9 promotes the proliferation of breast cancer and HCC cells [7,8]. In the study, we demonstrated that TMEM9 increased the proliferation and migration of LUAD.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…It has been reported that TMEM9 promotes the proliferation of breast cancer and HCC cells [7,8]. In the study, we demonstrated that TMEM9 increased the proliferation and migration of LUAD.…”
Section: Discussionsupporting
confidence: 54%
“…In the study, we investigated the expression and function of TMEM9 in LUAD and demonstrated that TMEM9 promoted tumor cell proliferation, migration, and angiogenesis via increasing VEGF expression and secretion. Recently, several studies have reported that TMEM9 was overexpressed in multiple cancers and significantly correlated with poor prognosis [8][9][10]. Our results showed that TMEM9 mRNA and protein expression in LUAD tissues was higher than those in normal peritumorial tissues.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Additionally, targeting HSPA8 by downregulating BCR-ABL can enhance the chemotherapy sensitivity of chronic myeloid leukemia cells [ 30 ]. The lysosomal TMEM9-LAMTOR axis has been found to play an important role in controlling mTOR signaling integrity in breast tumor development [ 31 ]. PSMD1 is a 26S proteasome subunit that regulates breast cancer cell growth by degrading p53 protein [ 32 ].…”
Section: Discussionmentioning
confidence: 99%